PENTINGNYA MANAJEMEN PERENCANAAN STRATEGIS BAGI SEORANG PEMIMPIN GEREJA - Sandi Bega (Sekolah Tinggi Teologi Duta Panisal, 2020)
One of the problems of an organization is because of the absence of management so that the organization does not grow healthy. Organizations that do not grow well are organizations that only run in place and eventually they will die. Therefore, every formof organization needs good and right management in order to grow and achieve the expected results. Management is a long-term commitment to something you want to do and regulate every activity carried out by the leader or subordinate so that it is well coordinated. Thus, the church which is an organization must have good and right management so that it becomes a healthy and growing church both in quality and quantity. The research method used in this study is a quantitative research method withthe percentage formula: P = (F X 100) / V (P = Percentage, F = Frequency, V = Number of valid questionnaires). This formula is used to analyze and manage the questionnaire data returned by respondents by calculating and looking at the percentage interpretation guidelines to determine the extent of the influence of the independent variables. Based on the results of research that departs from the research hypothesis